MO533: Safety of Roxadustat versus Erythropoiesis-Stimulating Agents for Treatment of Anemia in Patients With Chronic Kidney Disease Incident to or not Receiving Dialysis: Pooled Analysis of Four Phase 3 Studies. (3rd May 2022) - Barratt, Jonathan; Dellanna, Frank; Portoles, Jose; Choukroun, Gabriel; De Nicola, Luca; Reusch, Michael; Young, James; Dimkovic, Nada
Abstract: BACKGROUND AND AIMS: Patients with late-stage chronic kidney disease (CKD) who are non–dialysis-dependent (NDD) or incident to dialysis (ID) (e.g. initiated dialysis within the last 4 months) or dialysis-dependent (DD) represent a vulnerable population at increased risk for morbidity and mortality despite significant clinical advancements in recent years. The safety of roxadustat in patients with NDD or ID-DD CKD requires further elucidation. METHOD: In this post-hoc exploratory analysis, safety results from eligible patients with anemia of CKD enrolled in four phase 3, randomized, open-label studies [NDD (DOLOMITES) or ID-DD (SIERRAS, HIMALAYAS, ROCKIES)] were pooled and compared roxadustat to an erythropoiesis-stimulating agent (ESA). Endpoints were time to major adverse cardiovascular event [MACE; myocardial infarction, stroke and all-cause mortality (ACM)] and MACE+ (MACE plus congestive heart failure or unstable angina requiring hospitalization), ACM, and treatment-emergent adverse events (TEAEs). MACE and MACE + were evaluated for non-inferiority using hazard ratios (HRs) at 1.8 and 1.3-upper margins, respectively, and 95% confidence intervals (CIs). TEAEs were descriptively summarized. RESULTS: In total, 2142 patients were evaluated (1083 roxadustat; 1059 ESA; 616 NDD; 1526 ID-DD). Roxadustat was non-inferior to ESA for risk of MACE [HR 0.79 (95% CI 0.61–1.02)] and MACE+ [HR 0.78, (95% CI 0.62–0.98)] with a consistent finding for ACM [HR 0.78 (95% CI 0.57–1.05)]. TEAEs were generally comparable between roxadustat and ESA groups, including any TEAE [incidence rate per 100 patient-exposure years (IR/100 PEY) 56.1 versus 53.5], TEAEs leading to discontinuation of study drug (IR/100 PEY 6.7 versus 5.1) and TEAEs leading to death (IR/100 PEY 6.9 versus 7.4). The most frequent (IR/100 PEY) TEAEs were hypertension (roxadustat 12.8, ESA 12.3), end-stage kidney disease (roxadustat 6.6, ESA 6.1), diarrhea (roxadustat 7.1, ESA 4.8) and hyperkalemia (roxadustat 4.3, ESA 4.8). CONCLUSION: There was no evidence of an increased risk of cardiovascular events or mortality with roxadustat compared with ESA in patients with anemia who have NDD or ID-DD CKD. Although TEAE development occurred commonly in both the roxadustat and ESA groups, patients infrequently discontinued a study drug because of an adverse event.